ANALISIS PERBANDINGAN PENENTUAN HARGA POKOK PRODUKSI UNTUK MENENTUKAN HARGA JUAL PRODUK MENGGUNAKAN METODE FULL COSTING DAN VARIABLE COSTING - Febrianti, Riska; Rahmadani, Rahmadani (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
Determination of the cost of production is a way to take into account the elements of cost into the cost of production. Cost of Production is a collection of production costs consisting of direct materials, direct labor and factory overhead costs plus inventories of products in the initial process and less inventories of products in the final process. And the selling price is an estimate of the exchange rate of the product for money. The selling price is the price obtained from the sum of the total production costs plus the mark-up used to cover factory overhead costs. The purpose of this study is to analyze the comparison of the determination of the cost of production to determine the selling price of the product using the Full Costing and Variable Costing method. Based on the calculation of the cost of production to determine the selling price of the product using the Full Costing method and the calculation of the cost of production using the variable costing method Determination of the selling price of the method of calculating the cost of goods manufactured Full Costing is higher than the variable costing methode and the calculation of the cost of production of the variable costing method The difference in the unit selling price of this product occurs because the calculation of the cost of production is also different.